Agricultural land management, carbon reductions and climate policy for agriculture. Issue 6 (December 2012) - Muller, Adrian
Agriculture contributes to climate change and at the same time has a huge climate change mitigation potential – this lies mainly in increased soil carbon sequestration. This article discusses the mitigation potential of soil carbon sequestration, the underlying processes and main challenges for its utilization. There are difficulties of reliable quantification, aspects of leakage and system boundaries. Utilization of this mitigation potential is currently mainly via offset mechanisms. Due to the named challenges, offset mechanisms are not adequate for this and more aggregate approaches should be employed.